2016
DOI: 10.1007/s40037-016-0317-x
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perceptions of the patient-centredness of the learning environment

Abstract: BackgroundPatient-centred care is an important aspect of quality health care. The learning environment may impact medical students’ adoption of patient-centred behaviours.MethodsAll medical students at a single institution received an anonymous, modified version of the Communication, Curriculum, and Culture instrument that measures patient-centredness in the training environment along three domains: role modelling, students’ experience, and support for patient-centred behaviours. We compared domain scores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 17 publications
3
36
0
3
Order By: Relevance
“…being aware of own emotional responses) and taking into account support from family (52), when describing how they used insight gained from discussing the video cases. This finding is in accordance to recent research which indicates that medical students' adoption of patient-centeredness depends on their perception of the encouragement in clinical learning environments for applying patient-centered behaviors (53). Independency and clinical responsibility are considered important to develop students' competency during practice training (54,55).…”
Section: Active Roles Influencing Patient Centred Approaches In Studentssupporting
confidence: 89%
See 1 more Smart Citation
“…being aware of own emotional responses) and taking into account support from family (52), when describing how they used insight gained from discussing the video cases. This finding is in accordance to recent research which indicates that medical students' adoption of patient-centeredness depends on their perception of the encouragement in clinical learning environments for applying patient-centered behaviors (53). Independency and clinical responsibility are considered important to develop students' competency during practice training (54,55).…”
Section: Active Roles Influencing Patient Centred Approaches In Studentssupporting
confidence: 89%
“…It is well documented that students having negative experiences related to professional socialisation processes in clerkship may experience a major gap between preclinical and clinical training, regardless of the quality of the preclinical training (72). Their professional development may thus be prolonged, as these students get 'stuck' in the transition from theory to practice (68,73,74).The present study is in line with these findings, demonstrating how passive roles in clerkship compromises medical students' learning and development of a patient-centred approach (53,75). However, we did not specifically study how the psychiatric clerkships were organized or to what extent there were designated clinical supervisors with the role of guiding students' learning experiences.…”
Section: Facilitation By An Experienced Teacher and Resident Supportsupporting
confidence: 78%
“…Within dentistry, the real-time clinical environment and episodes of live patient care mean that clinical teachers are uniquely placed to role model for their students (Kenny et al 2003, Oandsan & Reeves 2005 or clinical teachers has been shown to impact on the ability of students to appreciate the importance of patient-centred care (Wilcox et al 2017).…”
Section: Situated Learning and Role-playmentioning
confidence: 99%
“…Ultimately, role modelling by fellow students or clinical teachers has been shown to impact on the ability of students to appreciate the importance of patient‐centred care (Wilcox et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Por isso, para alcançar mudança, as escolas precisam incorporar em seus currículos conhecimentos de ciências humanas e sociais. 13,18,19 cONclUsÃO Ao longo da pesquisa, percebeu-se que os estudantes se julgam preparados para estabelecer uma relação médico--paciente efetiva num modelo biologicista que considera a anamnese biológica mais relevante. Este preparo advém das disciplinas práticas e muitas vezes os aspectos técnicos da consulta são priorizados em detrimento da atenção integral do paciente.…”
Section: Contradição No Conceito De Saúdeunclassified